Utilizing Social Media as a Tool for Product Promotion to Boost Sales in E-Business Marketing - Wanda Eflinda Aryanti; Muhammad Iqbal Fasa (Jurnal Ekonomi Islam, 2025)
The development of technology today has accelerated rapidly, influencing many areas of human life, including the business world. Evolving technology has significantly changed human behavior in the modern era, especially with the rise of social media, which serves as a platform for sharing information and communicating between individuals. Today, social media has become like a second world for society. The widespread use of social media among the public creates a new market for businesses to market products digitally. This research analyzes various studies discussing similar themes, particularly the use of social media as a tool for digital marketing. The results aim to help the public understand that social media is one of the most effective methods for marketing a business because it can have a substantial impact at a low cost.